2018
DOI: 10.7554/elife.36209
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of long-term depression in the cerebellar flocculus during adaptation of optokinetic response

Abstract: Long-term depression (LTD) at parallel fiber (PF) to Purkinje cell (PC) synapses has been considered as a main cellular mechanism for motor learning. However, the necessity of LTD for motor learning was challenged by demonstration of normal motor learning in the LTD-defective animals. Here, we addressed possible involvement of LTD in motor learning by examining whether LTD occurs during motor learning in the wild-type mice. As a model of motor learning, adaptation of optokinetic response (OKR) was used. OKR is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Many previous studies, using various LTD-deficient animal models, have reported that synaptic plasticity at the PF-PC synapse is strongly correlated with motor learning (Boyden et al, 2006; De Zeeuw et al, 1998; Hansel et al, 2006). Optokinetic response (OKR)-induced synaptic LTD in the cerebellar cortex has been recently reported (Inoshita & Hirano, 2018), but plasticity induced by the VOR adaptation has yet to be proved. Late-phase LTD has also been implicated in VOR memory consolidation (Ahn, Ginty, & Linden, 1999; Boyden et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies, using various LTD-deficient animal models, have reported that synaptic plasticity at the PF-PC synapse is strongly correlated with motor learning (Boyden et al, 2006; De Zeeuw et al, 1998; Hansel et al, 2006). Optokinetic response (OKR)-induced synaptic LTD in the cerebellar cortex has been recently reported (Inoshita & Hirano, 2018), but plasticity induced by the VOR adaptation has yet to be proved. Late-phase LTD has also been implicated in VOR memory consolidation (Ahn, Ginty, & Linden, 1999; Boyden et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It is widely believed that the cellular basis of memory is derived from modifications of synaptic transmission, such as long-term potentiation (LTP) and long-term depression (LTD) (Kandel, Dudai, & Mayford, 2014). For decades, since Ito proposed the flocculus hypothesis (Ito, 1982), numerous studies have demonstrated that synaptic plasticity between parallel fibers (PFs) and cerebellar Purkinje cells (PCs) is the key mechanism of vestibule-ocular reflex (VOR) adaptation (De Zeeuw et al, 1998; Hansel et al, 2006; Inoshita & Hirano, 2018; Kakegawa et al, 2018; Schonewille et al, 2010). However, several works proposed that the synaptic plasticity at the PF-PC synapse is not sufficient to explain motor learning (Ito, 2013; Ke, Guo, & Raymond, 2009; Schonewille et al, 2011; Wulff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the idea that the cerebellum learns by sculpting away synapses that cause errors through this anti-Hebbian form of synaptic plasticity has had a powerful influence on the cerebellar field. LTD and its links to cerebellum-dependent learning have been extensively investigated, yet there is still much disagreement about whether and how LTD at parallel fiber-to-Purkinje cell synapses contributes to learning [6,7,1625,8,2630,915]. Here, we review findings that suggest a path toward a Clearer and more sophisticated understanding of the contribution of LTD to cerebellum-dependent learning.…”
Section: Main Textmentioning
confidence: 98%
“…A variety of recording, stimulation and perturbation approaches have yielded considerable, convergent evidence for a role of LTD in learning [10,11,3746,15,18,3136] but also yielded results that call into question the necessity of parallel fiber-to-Purkinje cell LTD for learning [13,40,41,4749]. One of the most widely used experimental approaches has been to employ pharmacological or molecular-genetic techniques to perturb LTD, and then test the effects on one or more cerebellum-dependent learning tasks.…”
Section: Main Textmentioning
confidence: 99%
“…This result predicts a reduced EPSCs in PF-PC synapses after HOKR adaptation. Indeed, a further study using conventional acute slice preparation showed the decrease in quantal EPSC amplitude of PF-PC synapses in the flocculus of mice after HOKR training, but the reduction was below 10%, much lower than the value expected from the reduction of AMPAR density 29 .…”
Section: Long-term Plasticity Induced By Hokr Adaptationmentioning
confidence: 91%